Energy status of chironomid larvae (Diptera: Chironomidae) from high alpine rivers (Tyrol, Austria) - Dvorak, Martin; Dittmann, Isabel L; Pedrini-Martha, Veronika; Hamerlik, Ladislav; Bitusik, Peter; Stuchlik, Evzen; Vondrák, Daniel; Füreder, Leopold; Lackner, Reinhard (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2023)
Chironomids (non-biting midges) inhabit almost every wet or semi-wet continental environment on Earth with probably 10,000 different species. Species occurrence and composition are undoubtedly limited by environmental harshness and food availability being reflected in their energy stores. Most animals store energy as glycogen and lipid. They enable the animals to survive adverse situations and to continue growth, development, and reproduction. This general statement is also true for insects and also particularly true for chironomid larvae. The rationale behind this research was, that probably any stress, any environmental burden, and any harmful influence increases the energy requirement of individual larvae depleting energy stores. We developed new methods to measure the glycogen and lipid content in small tissue samples. Here we show how to apply these methods to single chironomid larvae to demonstrate their energy stores. We compared different locations of the high Alpine rivers along harshness gradient densely populated and dominated by chironomid larvae. All samples show very low energy stores without any major differences. We found glycogen concentrations below 0.01% of dry weight (DW) and lipid concentrations below 5% of DW irrespective of the specific sampling point. These values are among the lowest ever observed in chironomid larvae. We demonstrate that individuals living in extreme environment are stressed leading to reduced energy stores in their bodies. This appears to be a general feature of high altitude regions. Our results provide new insights and a better understanding of population and ecological dynamics in harsh mountainous areas, also in view of a changing climate.
Keywords: Alpine streams; lipidy; Energy storage; Physiological indicator; Rivers; Chironomidae; Rakousko; Austria; larva; Glycogen; Chironomidae - Diamesa larvae; Animals; Lipids; zvířata; Larva; řeky